(untitled) (Research, Society and Development, 2021)
Objective: Evaluate the perceived change and identify the factors associated with it in users of the Psychosocial Care Centers for Alcohol and Other Drugs. Method: a cross-sectional study with 330 users of 13 Psychosocial Care Centers for Alcohol and Other Drugs in the State of Minas Gerais. The perception of change resulting from the treatment was identified using the Perceived Change Scale and the adjusted analysis of the data carried out using the least-squares linear regression model. Results: the prevalence of perceived change was 86.1%, with an average score of 2.62. Factors directly associated with the degree of perception of global improvement in multiple analysis: higher schooling (high school or complete technical course), attendance at the service, participation in group activities, and satisfaction with the service. The variables female gender, alcohol consumption, history of hospitalization, and complications during treatment showed less perception of improvement in care. Conclusions: the analysis of the factors associated with the evaluated constructs indicated a strong association of socioeconomic, clinical, process, and global satisfaction variables in determining the change perceived by users, aiming at changes in care that can influence the treatment involvement of users of psychoactive substances.